Microphysical and Kinematic Processes Associated With Anomalous Charge Structures in Isolated Convection. Issue 12 (16th June 2018) - Fuchs, Brody R.; Rutledge, Steven A.; Dolan, Brenda; Carey, Lawrence D.; Schultz, Christopher
Abstract: Microphysical and kinematic characteristics of two storm populations, based on their macroscale charge structures, are investigated in an effort to increase our understanding of the processes that lead to anomalous (or inverted charge) structures. Nine normal polarity cases (midlevel negative charge) with dual‐Doppler and polarimetric coverage that occurred in northern Alabama and six anomalous polarity cases (midlevel positive charge) that occurred in northeastern Colorado are included in this study. The results show that even though anomalous polarity storms formed in environments with similar instability, they had significantly larger and stronger updrafts. Moreover, the anomalous polarity storms evidently have more robust mixed‐phase microphysics, based on a variety of metrics. We infer positively charged graupel, and therefore high supercooled water contents, in the midlevels of the anomalous storms based on the relationship between colocations of graupel and inferred positive charge from Lightning Mapping Array data. Anomalous polarity storms in Colorado have much higher cloud base heights and shallower warm cloud depths in this study, leading us to hypothesize that anomalous polarity storms have lower amounts of dilution and entrainment. Using representative updraft speeds and warm cloud depths, the time required for a parcel to traverse from cloud base to the freezing level was estimated for each storm observation. We suggest that this metric is the key discriminator between the two storm populations and leads us to hypothesize that it strongly influences the amount of supercooled water and the probability of positive charge in the midlevels, leading to an anomalous charge structure. Key Points: Positively charged midlevel graupel is evident in anomalous polarity storms in concert with robust mixed‐phase microphysics Anomalous storms in Colorado have stronger and wider updrafts than normal polarity storms Warm cloud residence time appears to be a key discriminator between normal polarity storms and anomalous polarity storms